Reducing spray volume for the control of Leucoptera coffeella (Lepidoptera: Lyonetiidae) in coffee plants - Decaro Junior, Sergio Tadeu; Ferreira, Marcelo da Costa; Lasmar, Olinto; Fouquet, Gunther (Coffee Science - ISSN 1984-3909, 2015)
The present work evaluated reducing on spray volume for the control of Leucoptera coffeella (Guérin-Mèneville & Perrottet, 1842; Lepidoptera: Lyonetiidae) in coffee. Were used a conventional sprayer to apply the volumes 400 and 200 L ha-1 and an ultra-low-volume (ULV) sprayer to apply 46, 67 and 92 L ha-1. Sprays utilized 800 mL.ha-1 of the insecticide profenofos+lufenuron. The tracer MnSO4 was mixed to the spraying liquids at 20 g L-1. Leaves were collected from different parts of the coffee tree to evaluate the volume of insecticide spraying liquid deposited. For the L. coffeella control, leaves were collected before and 7, 14, and 21 days after spraying (DAS) to evaluate the number of live and dead L. coffeella larvae. The variables data were subjected to variance analysis and the means compared by Tukey’s test (p<0.05). There was no significant difference for spraying liquid deposit between the volumes of 200 and 400 L ha-1, as well as among the ULVs at 46, 67 and 92 L ha-1, however with lower deposit for the latter. The estimated insecticide volume deposited was significantly higher for the 200 L ha-1. The untreated control had higher number of live L. coffeella larvae compared to the sprays at 7 and 21 DAS, as exception for the 14 DAS. The volume of 200 L ha-1 by the conventional sprayer and 92 L.ha-1 by the ULV sprayer may be adopted for coffee plantations providing insecticide deposit and control of L. coffeella with efficiency above 80%.